2021
DOI: 10.1186/s12889-021-11564-4
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and correlates of comprehensive HIV/AIDS knowledge among adolescent girls and young women aged 15–24 years in Malawi: evidence from the 2015–16 Malawi demographic and health survey

Abstract: Background HIV epidemic remains a major public health issue in Malawi especially among adolescent girls and young women (AGYW). Comprehensive HIV/AIDS knowledge (defined as correct knowledge of two major ways of preventing the sexual transmission of HIV and rejection of three misconceptions about HIV) is a key component of preventing new HIV infections among AGYW. Therefore, the aim of this study was to identify the correlates of comprehensive HIV/AIDS knowledge among AGYW in Malawi. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 36 publications
12
17
1
Order By: Relevance
“…We discovered that, despite the progress made, knowledge remains low but still higher than in many other countries, with nearly half of respondents (53.6%) correctly answering the six HIV/AIDS-related questions in the RDHS. This is consistent with a study assessing knowledge in various SSA countries, which found that Rwandan women had a greater sense of comprehensive knowledge than women in other countries in the region [33,34]. The study's results also indicate that Rwandan adolescent girls are relatively knowledgeable about HIV/AIDS transmission modes.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…We discovered that, despite the progress made, knowledge remains low but still higher than in many other countries, with nearly half of respondents (53.6%) correctly answering the six HIV/AIDS-related questions in the RDHS. This is consistent with a study assessing knowledge in various SSA countries, which found that Rwandan women had a greater sense of comprehensive knowledge than women in other countries in the region [33,34]. The study's results also indicate that Rwandan adolescent girls are relatively knowledgeable about HIV/AIDS transmission modes.…”
Section: Discussionsupporting
confidence: 88%
“…Education was found to have a positive in uence on comprehensive knowledge of HIV/AIDS, with those having secondary level education being more knowledgeable than those with no education. This is not surprising given similar prior ndings in other countries such as Malawi [33], Kenya [35], Uganda [36],…”
Section: Discussionsupporting
confidence: 71%
“…This nding is in line with the studies done in Uganda, Ethiopia, and Malawi (13,16,25). Media has a great importance in creating awareness, enhancing knowledge, and changing health behavior of individuals as well as the community at large by delivering health information through the use of various channels (27).…”
Section: Discussionsupporting
confidence: 83%
“…They might have autonomy to decide on their health related aspects of life, and could access to health care services easily the other possible reason might be This might due to women attending secondary and higher education may get HIV related information either in the school curricula or in different extra-curricular activities like in different school clubs and education may also help people to be curious about their health as well as to seek information for their health. Educated women may search different information sources like the social media and internet web-sites of various organizations who are working targeted primarily on HIV which may help them to clear out misperceptions there by helping to develop comprehensive knowledge (13,24,25).…”
Section: Discussionmentioning
confidence: 99%
“…The inside of adolescents about HIV/AIDS with less is 48.7%, sufficient is 41%, and good is 10.3% [6]. Likewise, research on adolescent girls aged 15-24 years in Malawi found that 42.2% had comprehensive knowledge; the rest were still lacking [7]. Proper knowledge about HIV/AIDS is one of the factors in avoiding HIV transmission.…”
Section: Introductionmentioning
confidence: 99%